PENGARUH RISIKO AUDIT TERHADAP KUALITAS AUDIT MELALUI FEE AUDIT PADA KAP DI JAKARTA - Sucipto Sucipto; Titian Agustina (ITB AAS INDONESIA, 2022)
The aims of this study are (1) to analyze the effect of audit risk on audit fees in Jakarta, (2) to analyze the effect of audit risk on quality in Jakarta. (3) Analyze the effect of audit fees on audit quality in central Jakarta. (4) Analyze the effect of audit risk on audit quality through audit fees in Jakarta. The population in this study were public accounting firms in Jakarta, totaling 107 public accounting firms. From the total population, the research sample was used. The results show that 1 audit risk has an effect on audit fees, 2 audit risks have a negative effect on audit quality, 3 audit fees have an effect on audit quality, 4 audit risks have an effect on audit quality through audit fees at KAP West Jakarta.